Prosthesis in Anterior Cervical Herniated Disc Approach Does Not Prevent Radiologic Adjacent Segment Degeneration. Issue 15 (1st August 2020) - Yang, Xiaoyu; Donk, Roland; Arts, Mark P.; Bartels, Ronald H.M.A.; Vleggeert-Lankamp, Carmen L.A.
Abstract : Study Design: Retrospective analysis using data from RCTs. Objective: This study aimed to report on the incidence of radiological adjacent segment degeneration (ASD) in patients with cervical radiculopathy due to a herniated disc that were randomized to receive cervical arthroplasty or arthrodesis. Summary of Background Data: Cervical disc prostheses were introduced to prevent ASD in the postsurgical follow-up. However, it is still a controversial issue. Methods: Two hundred fifty-three patients were included in two randomized, double-blinded trials comparing anterior cervical discectomy with arthroplasty (ACDA), with intervertebral cage (ACDF), or without intervertebral cage (ACD) for one-level disc herniation. Neutral lateral radiographs were obtained preoperatively, at 1- and 2-year follow-up after surgery. Radiological ASD was evaluated on X-ray and defined by a decrease in disc height and the presence of anterior osteophyte formation on both the superior and the inferior level in relation to the target level. Results: Radiological ASD was present in 34% of patients at baseline and increased to 59% at 2-year follow-up in the arthrodesis groups (ACD and ACDF combined), and to 56% in the arthroplasty group. Progression of radiological ASD was present in 29% of patients in the arthrodesis group and in 31% of patients in the arthroplasty group for 2-year follow-up. Conclusions: Radiological ASD occurs in a similar manner in patients who were subjected to arthrodesis in cervical radiculopathy and in patients who received arthroplasty to maintain motion. Current data tend to indicate that the advantage of cervical prosthesis in preventing radiological ASD is absent. Level of Evidence: 2 Abstract : It is still a controversial issue that whether cervical disc prostheses can prevent adjacent segment degeneration. In this study, current data tend to indicate that the advantage of cervical prosthesis in preventing radiological adjacent segment degeneration is absent.